The Effect of Active Learning Model of Quiz Team Type on the Learning Outcomes of Students - Ilham Assidiq; Dian Firdiani; Elihami Elihami; Jamaluddin Ahmad; Yunus Busa (Universitas Muhammadiyah Enrekang, 2022)
This study is a quasi-experimental study that aims to determine the existence of positive effects of active learning type quiz team of student learning outcomes with